(untitled) (Zaporizhzhia Historical Review, 2021)
The article is analyzed Ukrainian Social Democratic Labour party’s position about regime of Ukrainian Republic in the period of Durektoria UNR. The author shows evolution in party’s views of this from recognition “labor principle” of organization to parliamentarism.